Differences in the Degree of Spasticity in Post-Haemorrhagic and Non-Haemorrhagic Stroke Patients Based on the Modified Ashworth Scale - Ifandias Gian Abhista; Maria Belladonna Rahmawati Sugianto; Tanti Ajoe Kesoema; Trianggoro Budisulistyo (RSUP Dr. Kariadi, 2024)
Background : Stroke is a brain function disorder caused by vascular disturbances with manifestations ranging from paralysis to death. Stroke is a health issue with high incidence and mortality rates. Furthermore, post-stroke patients can experience various residual symptoms such as spasticity, which can lead to decreased productivity and socio- economic impacts. Spasticity is a common symptom in stroke survivors, with a prevalence ranging from 30% to 80%. This symptom typically appears several weeks after a stroke and can persist for up to 12 months, causing reduced productivity and socio-economic challenges. Hemorrhagic strokes result from blood vessel rupture, while non- hemorrhagic strokes are caused by ischemia. Both types can damage motor pathways, leading to spasticity. Understanding the differences in spasticity severity between stroke types may guide targeted rehabilitation strategies. The aimsof ths study was to determine the difference in the degree of spasticity in post-stroke patients between hemorrhagic and non-hemorrhagic strokes based on the Modified Ashworth Scale. Methods : An analytical observational study with a cross-sectional design was conducted. The study included 33 post-hemorrhagic stroke patients and 33 post-non- hemorrhagic stroke patients. The degree of spasticity was measured using the Modified Ashworth Scale. Statistical analysis was performed using the Chi-Square test. Results : The Chi-Square test for the variable